Daytime depth and thermal habitat of two sympatric krill species in response to surface salinity variability in the Gulf of St Lawrence, eastern Canada - Plourde, Stéphane; McQuinn, Ian H.; Maps, Frédéric; St-Pierre, Jean-François; Lavoie, Diane; Joly, Pierre (ICES Journal of Marine Science, 2013)
Abstract Plourde, S., McQuinn, I. H., Maps, F., St-Pierre, J-F., Lavoie, D., and Joly, P. 2014. Daytime depth and thermal habitat of two sympatric krill species in response to surface salinity variability in the Gulf of St Lawrence, eastern Canada. – ICES Journal of Marine Science, 71: 272–281. We describe the response of acoustically determined weighted mean depth (WMD) of two sympatric species of krill, Thysanoessa raschii and Meganyctiphanes norvegica, to variations in surface salinity during summer in the Gulf of St Lawrence. In this coastal system, non-living particulates and CDOM carried by the freshwater run-off of the St Lawrence River and several large rivers have a strong impact on turbidity and light attenuance in the surface layer. The WMD of T. raschii and M. norvegica were significantly and positively related to surface salinity. However, M. norvegica was found deeper and in warmer water than T. raschii, and the latter had a steeper response to surface salinity. The species-specific relationships between daytime WMD and surface salinity enabled us to estimate both species regional and interannual variations in summertime temperature habitat during a 21-year period (1991–2011). The variability in daytime WMD resulted in significant inter- and intraspecific differences in the temperature experienced by adult krill that may impact development, growth, and reproduction. Our study illustrated the importance of considering species-specific responses to environmental forcing in coupled biophysical models that aim to explore the impacts of environmental variations on krill dynamics.